Neurocognitive and behavioral basis of performing simple and complex movements, imitations and practices in children with autism spectrum disorder - Zrnić, Lana (PONS - medicinski časopis, 2023)
Imitation of simple movements is the basis for all kinds of learning. It is a necessary prerequisite for symbolic functioning and functioning in the social environment. The motor execution of imitation movements is at an unsatisfactory level, in children with an autistic spectrum disorder, especially in the domain of movement. By reviewing the relevant literature from both aspects: neurocognitive and behavioral, we get the data on the motor functioning of children with autism spectrum disorders. Based on the results of the research, children with autism spectrum disorders show reduced activity in certain regions, especially in the areas of the frontal and parietal lobes. When conducting motor tests of imitation and practice, children from this population show more errors in performing repetitive movements. By looking at the overall functioning of people with autism, especially their neurocognitive functions and their behavior, we can discover new ways for interventions and for therapeutic work with these people.